Digitalization of Islamic Banking in Indonesia: Justification and Compliance to Sharia Principles - Ichsan, Muchammad; Fitriyanti, Fadia; Setiorini, Kusumaningdiah Retno; Al-Qudah, Adam Ma'abdeh (Jurnal Media Hukum, 2024)
Technological sophistication is observed to be increasing the necessity for digitalization of Islamic banks in Indonesia to avoid being abandoned by their customers, as conventional banks rapidly advance their digital offerings and set higher expectations for financial services. However, these banks are required to comply with Sharia principles for their products and services. This study was conducted to analyze the justification of digitalization of Islamic banking system and compliance of the digital services implemented to Sharia principles. It employed doctrinal legal study methods. Data were retrieved from literature references and were analysed qualitatively using a conceptual and statutory approach. The results showed several reasons to justify digitalization of Islamic banking system and these include the current demand for digital products and services, the prevalence of the millennial generation, and the legal backing provided for the advancement in Indonesia. These principles mandate that Islamic banks must avoid practices involving maisir (gambling), gharar (obscurity), haram (prohibited activities), riba (usury), and zalim (injustice). This study is novel in its comprehensive analysis of how digitalization can be harmonized with Sharia principles in the Indonesian context, providing a unique legal and practical framework for Islamic banks aiming to modernize their services while maintaining religious compliance.